Investigating the Impact of Media Alerts on an Epidemiological Model Involving Asymptomatic Cases - Saadi, Rami Raad; Al-Husseiny, Hassan F. (Iraqi Journal of Science, 2024)
The significance of media alerts in influencing public perception and response during disease outbreaks is of paramount importance. This research investigates how media alerts affect the epidemiological model by taking into account both asymptomatic and symptomatic cases. Media alerts serve as a powerful tool for raising awareness about the disease, driving people to undergo testing and diagnosis, and promoting adherence to public health measures. This, in turn, contributes to better reporting and surveillance of cases, leading to a more accurate representation of disease spread in the model. The proposed model introduces a five-dimensional compartment system that includes susceptible, asymptomatic, symptomatic, recovered populations and media. This research addresses various aspects of the model, such as its uniqueness, boundedness, and existence of solutions. The determination of all possible model equilibrium points is thoroughly explored. To study the global dynamics of the proposed models, appropriate Lyapunov functions are employed. Additionally, numerical simulation is also carried out to investigate the influence of parameters affecting the dynamics of the model and to support the gathered analytical findings of the model.